2022
DOI: 10.1038/s41385-022-00543-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin U promotes human type 2 immune responses

Abstract: Type 2 immunity mediates the immune responses against parasites and allergic stimuli. Evidence from studies of cell lines and animals implies that neuromedin U (NmU) acts as a pro-inflammatory mediator of type 2 inflammation. However, the role of NmU in human type 2 immunity remains unclear. Here we investigated the expression of NmU in human blood and airways, and the expression of NmU receptors by human immune cells in blood and lung tissue. We detected human NmU (hNmU-25) in blood and airways with higher co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…As a major receptor of NMU which was already considered as a tumor growth and/or progression marker in endometrial, renal, and breast cancers, NMUR1 could interact with NMU leading to autocrine tumor-promoting pathway activation, including intracellular Caflux, the phosphorylation of ERK1/2 kinases and hypoxia-inducible factors activation. 9 , 10 , 11 Considering that NMUR1 was mainly expressed in peripheral tissues especially in gut and lung, 1 , 5 , 52 NMUR1 was widely reported to be involved in airway inflammation and immune response, 15 , 53 while few literatures revealed the association between NMUR1 and gastrointestinal immune response, especially in gastrointestinal cancer. Our study identified NMUR1 as a potential biomarker for CRC prognosis and immunotherapy response by combining multi-omics analyses and in vitro functional experiments.…”
Section: Discussionmentioning
confidence: 99%
“…As a major receptor of NMU which was already considered as a tumor growth and/or progression marker in endometrial, renal, and breast cancers, NMUR1 could interact with NMU leading to autocrine tumor-promoting pathway activation, including intracellular Caflux, the phosphorylation of ERK1/2 kinases and hypoxia-inducible factors activation. 9 , 10 , 11 Considering that NMUR1 was mainly expressed in peripheral tissues especially in gut and lung, 1 , 5 , 52 NMUR1 was widely reported to be involved in airway inflammation and immune response, 15 , 53 while few literatures revealed the association between NMUR1 and gastrointestinal immune response, especially in gastrointestinal cancer. Our study identified NMUR1 as a potential biomarker for CRC prognosis and immunotherapy response by combining multi-omics analyses and in vitro functional experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NMU was shown to activate ILC2s during a viral respiratory infection [ 64 ]. In a human study, NMU increased the levels of IL-5 and IL-13 derived from human ILC2s in a dose-dependent manner and induced cell migration, including eosinophils [ 65 ]. Calcitonin-gene-related peptide (CGRP) is released from pulmonary neuroendocrine cells (PNECs) that reside near ILC2s at airway branchpoints [ 66 ].…”
Section: Modulators Of Ilc2 Function In Asthmamentioning
confidence: 99%
“…NMU directly induces ILC2 proliferation and production of IL-5, IL-9, and IL-13, and amphiregulin to protect against helminth infection. Nmur 1 is also expressed on other type 2 immune cells including Th2 and eosinophils, and NMU elicits migration of type 2 immune cells ( 98 ). Mucosal neurons are located adjacent to ILC2s, and these neurons directly sensed worm products and alarmins to induce NMU, leading to the production of innate type 2 cytokines ( 97 ), while CGRP antagonizes many actions of NMU and IL-33 but promote IL-5 production ( 99 ).…”
Section: Introductionmentioning
confidence: 99%